ANALISIS KETERLAKSANAAN PKH DAN DAMPAKNYA TERHADAP KESADARAN ORANG TUA TERKAIT KESEHATAN DAN PENDIDIKAN DI KECAMATAN SELAPARANG KOTA MATARAM ) - syamsiar, huldiya (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2017)
Abstract PKH (program harapan keluarga)  is the social protection for poor society. In this case, selaparang subdistrict is one of subdistrict that be a place for helping by PKH that participants was obligated for filling regulations and filling obligations for poor household who in PKH. PKH is one of rank program that expected by society because it was helping living of poor household in improving the living in education and healty. This research aimed to know the process of action of PKH that in selaparang  subdistrict that began from the program that  offered to society until the effect for awarne of parent about healty and education for child. This research use qualitative method with descriptive aproachment. Location of the research is in nine politic distric that in selaparang subdistrict in mataram city. The technique of collecting for data is observation, interview and documentation. Data analysis that use by this research is reduction data. Data presentation, making the congclution, verification, data validation done with using tringulation technique. The result of this research is PKH in selaparang  subdistrict was good from data collection until the last process although there was weakness. There were programs that was offered :  1) Obligation for school until nine year 2) Healty service for a mother who pregnant, childbrith, baby and toddler, 3) Money that is taken at the second stage of PKH. This program will make awarness for parent to always improve child attendance and quality of child healty with always checking every month for baby helaty to service center for healty.Key word : PKH, Parent Awareness, The Important Of Education, Healthty, Poor Family